Frontal Lobe Epilepsy in a Pediatric Population: Characterization of Clinical Manifestations and Semiology - Dajeong Lee; Jiwon Lee; Jeehun Lee (Korean Child Neurology Society, 2022)
Purpose Frontal lobe epilepsy (FLE) has various clinical presentations depending on the anatomy involved. Seizures are brief and can mimic psychiatric conditions, and patients often cannot describe the aura. Therefore, it is difficult to characterize the semiology, especially in pediatric patients. This study investigated the characteristics of pediatric FLE. Methods We retrospectively reviewed the data of pediatric patients with FLE who underwent long-term video-electroencephalography (EEG) monitoring between January 2010 and June 2020. Patients' demographic data, seizure-related clinical presentations, semiology, brain magnetic resonance imaging (MRI), and EEG data were analyzed. Results Fifty-six patients were included (31 males, 25 females). The age of seizure onset varied from 1 month to 14 years (mean±standard deviation, 6.1±4.4 years). Seizures were classified into nine categories, including focal tonic (30/56), aura (22/56), hypermotor (17/56), focal clonic (15/56), versive (13/56), and bilateral asymmetric tonic (4/56). Seventeen patients (30.4%) had abnormal MRI results, including focal cortical dysplasia, heterotopic gray matter, and neuroepithelial tumors. Ictal EEG changes were commonly observed in the dorsolateral premotor and central cortices. In focal tonic seizures, EEG changes often originated in the premotor cortex. The location of the lesions on MRI and EEG coincided in six cases. Conclusion In pediatric FLE, various seizure types occur depending on the ictal anatomic origin, and individual patients had multiple semiologies. Brain MRI was normal in two-thirds of patients, and interictal EEG did not reveal epileptiform discharges in approximately 25%. Semiology reported on the basis of home videos and interictal EEG will help localize the ictal onset zone.